Analisis Praktik Akuntansi EMKM (Studi pada Usaha Coffee Shop XYZ) - Daulay, Anggi Anugerah (JURNAL INFO ARTHA, 2024)
This research discusses the problems of micro, small, and medium enterprises (MSMEs) in carrying out financial recording and reporting. This research takes a case study of accounting practices in the XYZ coffee shop business. The case study on XYZ aims to discuss the process of recording and preparing financial statements which are then compared with Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). Applying qualitative descriptive methods through interviews and documentation techniques, this research shows that XYZ has not implemented accounting practices that are in line with SAK EMKM. XYZ needs to start presenting inventory accounts in the statement of financial position and prepare notes to the financial statements which state that the entity adopts accounting policies based on SAK EMKM.